2010
DOI: 10.4097/kjae.2010.58.2.184
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gabapentin pretreatment on brain injury induced by focal cerebral ischemia/reperfusion in the rat

Abstract: BackgroundExperimental studies have shown that gabapentin can reduce neuronal injury in the setting of cerebral ischemia, but the mechanisms have not yet been clearly determined. This study was conducted to determine whether gabapentin pretreatment altered expression levels of heat shock protein 70 and reduced acute phase neuronal injury in rats subjected to transient focal cerebral ischemia/reperfusion.MethodsForty male Sprague-Dawley rats (260-300 g) were randomly assigned to one of four groups (saline-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Potential mechanisms that may contribute to central sensitization include increased N‐methyl‐ d ‐aspartic acid (NMDA) and α ‐amino‐3‐hydroxyl‐5‐methyl‐4‐isoxazole‐propionate (AMPA) receptor‐mediated excitatory synaptic transmission in the dorsal horn; a decrease in γ ‐aminobutyric acid (GABA) and glycine receptor‐mediated inhibitory synaptic transmission; an increase in descending facilitation; [31–33] it is possible these mechanism may be involved in the development of post‐stroke allodynia observed in this study. It is reported that the increase of synaptic glutamate or excess influx of calcium ion into neuronal cells following NMDA‐receptor activation significantly exacerbated the development of infarction [34,35] . As described above, similar molecules are known to be involved in the mechanism of development of pain [25,36] .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Potential mechanisms that may contribute to central sensitization include increased N‐methyl‐ d ‐aspartic acid (NMDA) and α ‐amino‐3‐hydroxyl‐5‐methyl‐4‐isoxazole‐propionate (AMPA) receptor‐mediated excitatory synaptic transmission in the dorsal horn; a decrease in γ ‐aminobutyric acid (GABA) and glycine receptor‐mediated inhibitory synaptic transmission; an increase in descending facilitation; [31–33] it is possible these mechanism may be involved in the development of post‐stroke allodynia observed in this study. It is reported that the increase of synaptic glutamate or excess influx of calcium ion into neuronal cells following NMDA‐receptor activation significantly exacerbated the development of infarction [34,35] . As described above, similar molecules are known to be involved in the mechanism of development of pain [25,36] .…”
Section: Discussionmentioning
confidence: 92%
“…It is reported that the increase of synaptic glutamate or excess influx of calcium ion into neuronal cells following NMDA-receptor activation significantly exacerbated the development of infarction. [34,35] As described above, similar molecules are known to be involved in the mechanism of development of pain. [25,36] Thus, some drugs such as NMDA-receptor antagonists and calcium channel blockers would be effective in inhibiting the development of infarction as well as development of post-stroke allodynia.…”
Section: Discussionmentioning
confidence: 99%
“…Most strokes are ischemic and cause injury to a specific region of the brain by restriction of blood flow (Dhiraj et al, 2013). The incidence of stroke in the United States affects between 500,000 and 750,000 people annually, especially those over 65 years old (Kim et al, 2010). There are several important risk factors that contribute to cerebral ischemia, among them are hypertension, smoking, sedentary lifestyle and obesity (Bronner et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…[11] Gabapentin, which has entered into clinical use as an adjuvant anticonvulsant drug in the treatment of partial seizures in 1993, is widely used for neuropathic pain, migraine, and spasticity today. [12][13][14] The antinociceptive, anticonvulsant, anxiolytic, and neuroprotective effects of gabapentin have been shown in various animal models. [15] It has been suggested that the neuroprotective effects of gabapentin may be related to changes in glutamate synthesis and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…[15] It has been suggested that the neuroprotective effects of gabapentin may be related to changes in glutamate synthesis and metabolism. [13,16] There are many studies investigating its neuroprotective effects in cerebral ischemia, cerebral trauma, spinal cord trauma, and peripheral nerve injury.…”
Section: Introductionmentioning
confidence: 99%